2001
DOI: 10.1021/bi001988c
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Antagonists Are Potent Inhibitors of Mast Cell Tryptase

Abstract: Tryptase may be a key mediator in mast cell-mediated inflammatory reactions. When mast cells are activated, they release large amounts of these tetrameric trypsin-like serine proteases. Tryptase is present in a macromolecular complex with heparin proteoglycan where the interaction with heparin is known to be essential for maintaining enzymatic activity. Recent investigations have shown that tryptase has potent proinflammatory activity, and inhibitors of tryptase have been shown to modulate allergic reactions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 31 publications
5
40
0
3
Order By: Relevance
“…Tryptase is one of the most powerful angiogenic mediators released by human MCs and it may be angiogenic via several mechanisms (23)(24)(25)(26). Blair et al have demonstrated that direct addition of tryptase to microvascular endothelial cells cultured on Matrigel caused a pronounced increase of capillary growth, which was suppressed by specific tryptase inhibitors, and directly induced endothelial cell proliferation in a dose-dependent fashion (10).…”
Section: Discussionmentioning
confidence: 99%
“…Tryptase is one of the most powerful angiogenic mediators released by human MCs and it may be angiogenic via several mechanisms (23)(24)(25)(26). Blair et al have demonstrated that direct addition of tryptase to microvascular endothelial cells cultured on Matrigel caused a pronounced increase of capillary growth, which was suppressed by specific tryptase inhibitors, and directly induced endothelial cell proliferation in a dose-dependent fashion (10).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for the formation of active tryptase monomers apparently involves interaction with heparin, similar to the generation of tetrameric tryptase. The continuous presence of heparin is known to be essential for maintaining the activity of tetrameric tryptase, and interfering with the interaction of tryptase with heparin leads to tetramer dissociation along with enzymatic inactivation (23). A possible explanation for this would be that heparin is needed for bridging the tryptase subunits (see above and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is noteworthy that heparin-binding compounds (e.g. polycations) are strongly inhibitory for mast cell tryptase, apparently by competing with tryptase for binding to heparin (23,24). It has also been suggested that the presence of heparin is required in the autocatalytic processing of protryptase to mature tryptase monomer (25).…”
mentioning
confidence: 99%
“…The chemokine has been previously suggested as a potential candidate as a heparin antagonist to effect ␤-tryptase inhibition by Pejler and colleagues (8,55). In fact, in our experiments we found that CXCL4 dose-dependently inhibits ␤-tryptase, exhibiting IC 50 values between 14 and 1.3 M. These results are comparable to the described efficacy of other heparin antagonists to ␤-tryptase, e.g., 3.6, 16, 65, and more than 24 M for polybrene, myeloperoxidase, protamine sulfate, and lactoferrin, respectively (11,12,55,56). As destabilization of ␤-tryptase by CXCL4 strongly depends on the concentration and type of heparin added for complexation of the enzyme, it was an interesting result that inhibition required a 4-fold excess of CXCL4 over 15-kDa heparin (ratio of IC 50 to c(Heparin) of 4.4, 2.9, and 3.8).…”
Section: Discussionmentioning
confidence: 99%